Patient-focused goal planning process and outcome after spinal cord injury rehabilitation: Quantitative and qualitative audit. - Byrnes, M.; Beilby, Janet; McLennan, R.; Ker, J.; Schug, S.; Ray, P. (Sage Publications Ltd, 2012)
Objective: To evaluate the process and outcome of a multidisciplinary inpatient goal planning rehabilitation programme on physical, social and psychological functioning for patients with spinal cord injury. Design: Clinical audit: quantitative and qualitative analyses. Setting: Specialist spinal injury unit, Perth, Australia. Subjects: Consecutive series of 100 newly injured spinal cord injury inpatients. Main measure(s): The Needs Assessment Checklist (NAC), patient-focused goal planning questionnaire and goal planning progress form. Results: The clinical audit of 100 spinal cord injured patients revealed that 547 goal planning meetings were held with 8531 goals stipulated in total. Seventy-five per cent of the goals set at the first goal planning meeting were achieved by the second meeting and the rate of goal achievements at subsequent goal planning meetings dropped to 56%. Based on quantitative analysis of physical, social and psychological functioning, the 100 spinal cord injury patients improved significantly from baseline to discharge. Furthermore, qualitative analysis revealed benefits consistently reported by spinal cord injury patients of the goal planning rehabilitation programme in improvements to their physical, social and psychological adjustment to injury. Conclusions: The findings of this clinical audit underpin the need for patient-focused goal planning rehabilitation programmes which are tailored to the individual’s needs and involve a comprehensive multidisciplinary team.